2012
DOI: 10.1007/s13365-012-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of white matter injury in HIV infection after partial immune reconstitution: a DTI tract-based spatial statistics study

Abstract: HIV infected individuals with severe immune suppression are more likely to develop HIV-associated neurocognitive disorders than those with preserved immune function. While partial immune reconstitution occurs in those with severe immune suppression after starting combined antiretroviral therapy, it is not established whether improvement in immune function reverses or prevents injury to the central nervous system (CNS). To address this question, 50 participants (nadir CD4 counts ≤200cells/mm3, on a stable antir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
89
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 44 publications
(58 reference statements)
15
89
2
Order By: Relevance
“…FA value and ADC value, which is more sensitive to changes of white matter in HIV þ patients is an contradiction at previous reports. We found HIV þ infection affects ADC to a greater extent than FA, which may suggest that alteration of ADC may reflect the prominent disease process in HIV þ patients, this is consistent with the findings of Zhu T et al [24], they reported that mean diffusivity (MD) increased significantly in the both hemispheres in HIV patients with neurologically asymptomatic compared to controls, no statistical significance was detected in any regions in FA.…”
Section: Rois Groupssupporting
confidence: 91%
“…FA value and ADC value, which is more sensitive to changes of white matter in HIV þ patients is an contradiction at previous reports. We found HIV þ infection affects ADC to a greater extent than FA, which may suggest that alteration of ADC may reflect the prominent disease process in HIV þ patients, this is consistent with the findings of Zhu T et al [24], they reported that mean diffusivity (MD) increased significantly in the both hemispheres in HIV patients with neurologically asymptomatic compared to controls, no statistical significance was detected in any regions in FA.…”
Section: Rois Groupssupporting
confidence: 91%
“…In the HIV context and based on DTI acquisition parameters, we interpret FA as relating to the degree of axonal structural integrity primarily reflecting membrane and cytoskeleton integrity (Winston 2012) and possibly astrocytic structural integrity (Lentz et al 2014). MD reflects aspects of WM microstructure density (Winston 2012;Zhu et al 2013), such as degree of extracellular space between WM tracts (Lentz et al 2014) that may be affected by neuroinflammation including glial involvement and myelin loss to a lesser extent. In this case, myelin contribution to MD changes is debatable (Lentz et al 2014) as massive demyelination is not a common feature of HIV-related brain injury even in those who had severe HIV encephalopathy (Pelle et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The findings that FA values within the genu, body, and splenium of the corpus callosum were reduced in HIV-positive adolescents are consistent with findings in previous studies on HIV-infected children and adults. For example, FA values for the genu, 10 body, 21 and splenium 8 of the corpus callosum 11,22 are significantly reduced in HIV-infected adults. Decreased FA of the body of corpus callosum is also reported in HIV-infected children.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, deceased FA is also found in the anterior and superior corona radiata in HIV-infected participants. 10,11 The anterior corona radiata is associated with functions of the executive network. 26 Previous studies have focused on HIV-infected children and found that the subjects displayed visual-spatial memory and motor developmental deficits and executive function disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation